Probabilistic Seismic Hazard Analysis Assessment in Cianjur Following the Mw 5.6, 2022 Earthquake - Ardha, Yusufa Kholifa; Satyarno, Iman; Marliyani, Gayatri Indah (Journal of the Civil Engineering Forum, 2025)
On November 21, 2022, a Mw 5.6 earthquake struck Cianjur, West Java, Indonesia, causing extensive damage to buildings, infrastructure, and public facilities, and resulting in 602 fatalities and thousands of injuries. The earthquake’s hypocenter was located near the Cugenang Sub-District, leading to the identification of the previously unmapped Cugenang Fault as its source. This discovery highlights the need to reassess seismic hazards in the region, as it reveals the existence of previously unrecognized active faults. This study conducts a probabilistic seismic hazard analysis (PSHA) for Cianjur using an updated seismic source model that incorporates the Cugenang Fault. We apply updated ground motion prediction equations (GMPEs) and utilize the logic tree method to account for uncertainties in attenuation equations and source parameters. Ground motion is expressed as peak ground acceleration (PGA) on both bedrock and surface conditions for return periods of 100, 150, 250, 500, 1,000, 2,500, 5,000, and 10,000 years. These return periods capture the hazard levels associated with both frequent low-magnitude and rare high-magnitude earthquakes. Our findings indicate that high PGA values in the Cianjur area are concentrated around crustal faults, exceeding 1.0 g for return periods of 2,500 years and beyond. The Cugenang Fault has a localized impact, with its influence extending up to approximately 10 km from the fault line. A seismic hazard disaggregation analysis confirms that crustal faults are the dominant seismic sources in the region. The results of this study provide valuable insights for updated seismic risk in Cianjur and support future mitigation strategies, urban planning, and infrastructure design to enhance earthquake resilience in the affected area.